Inequality of women in the labor market in the context of the green economy - Ostojić Ivana; Maksimović Marijana; Stojković-Zlatanović Sanja (Temida)
Society and economies face the necessity of social, political and, consequently, legal addressing of discrimination based on different personal characteristics, such as gender, race, language, political opinion, national origin, and ethnic and social status. In this regard, it is possible to look at, especially from the conceptual-theoretical, as well as the accompanying applicative aspect, and give a conceptual demarcation of (gender) equality in relation to the institute of women‘s inequality as an established vulnerable category in workplaces. For many years throughout history in traditional and patriarchal societies, women had a subordinate position with an emphasis on the dominance of the paternalistic concept of man‘s position in the world of work. However, in the last decade, as more is being written, spoken, and more research is being conducted on the subject of discrimination at work, efforts have been made to solve this problem. The latest trends related to the transition to a green economy also aim to promote the importance and necessity of mitigating factual inequality between the sexes with legal measures deriving from the principle of equal opportunities and procedures in employment and work. The subject of this analysis is an overview of gender inequalities in the labour market, Norway, Slovenia and Serbia, which were taken as examples of good practices in the period from 2015 to 2021. The comparison is made with a focus on the current concept of promoting a green economy and sustainable development. The goal of the paper is to determine whether the green economy is a chance to alleviate inequality and increase equality in the labour market, or whether it carries limitations that can hardly be overcome when it comes to the world of work.